2012
DOI: 10.1016/j.neulet.2012.03.079
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptor subunit expression in the cuneate nucleus of adult squirrel monkeys after peripheral nerve injury

Abstract: The primate somatosensory system provides an excellent model system with which to investigate adult neural plasticity. Here, we report immunohistochemical staining data for the GluR1 and GluR2/3 AMPA receptor subunits in the cuneate nucleus of adult squirrel monkeys one week after median nerve compression. These data are compared to subunit changes in the area 3b cortex of the same animals. We report differences between control and deprived brainstem implying that deprivation induced changes in subunit express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Specifically, we have investigated receptor subunit specific changes that occur within the cortex and brainstem during recovery from peripheral nerve compression. [45, 46, 47, 51]. The current study extends these investigations of AMPA and GABA receptor subunits to the cuneate nucleus one and five months after nerve compression.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Specifically, we have investigated receptor subunit specific changes that occur within the cortex and brainstem during recovery from peripheral nerve compression. [45, 46, 47, 51]. The current study extends these investigations of AMPA and GABA receptor subunits to the cuneate nucleus one and five months after nerve compression.…”
Section: Introductionsupporting
confidence: 65%
“…Previously we have reported that brainstem and cortex undergo a period of developmental recapitulation around 1 week after nerve injury [45, 46, 51]. Developmental plasticity happens considerably faster (hours/days) than more prolonged forms of adult plasticity (weeks/months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to LTP, in which CP-AMPARs are incorporated into the synaptic membrane during the initial stage of targeted synaptic strengthening (Plant et al, 2006;Yang et al, 2010), more widespread synaptic incorporation of CP-AMPARs occurs in response to suppression of excitatory input to neurons in culture (Thiagarajan et al, 2005(Thiagarajan et al, , 2007Lee, 2012;Kim & Ziff, 2014) and cortical and brainstem sensory neurons in vivo (Goel et al, 2011;Jitsuki et al, 2011;Sarin et al, 2012). This homeostatic synaptic scaling is triggered by decreased Ca 2+ signaling (Thiagarajan et al, 2002;Kim & Ziff, 2014), and decreased activity of the Ca 2+ -dependent phosphatase, calcineurin, which normally dephosphorylates pSer845-GluA1 and enables endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…2002). This is followed by a subsequent phase of “developmental recapitulation” during which critical period like receptor expression (plasticity) is re-expressed in the deprived sensory neuraxis (Mowery and Garraghty, 2009; Mowery et al, 2011; Sarin et al, 2012). This phase could prime the cortex for the NMDA receptor-dependent stage of reorganization (Garraghty et al, 2006; Garraghty and Muja, 1996; Mowery et al, 2013; 2014 Myers et al, 2000).…”
Section: Introductionmentioning
confidence: 99%